1997
DOI: 10.1046/j.1365-2141.1997.d01-2090.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mdr1 and mrp in the normal B‐cell homologue of B‐cell chronic lymphocytic leukaemia

Abstract: Summary. B-cell chronic lymphocytic leukaemia (CLL) cells commonly express the multidrug resistance phenotype. The aim of this study was to establish whether the normal homologue in B-cell ontogeny of B-CLL also expressed the multidrug resistance (mdr) phenotype. Human tonsillar lymphocytes were sorted to yield two B-cell subsets based on the expression of CD19, CD5 and CD10. The normal homologue was represented by a population of B cells that was CD19 positive, CD10 negative and weakly expressed CD5. Based up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In B-CLL, P-glycoprotein expression is felt to be intrinsic rather than acquired, reflecting different basal levels of MDR1 expression in the different lymphocyte subsets [16,28,29]. Some of this intrinsic expression may vary as a result of differential influences of hormone levels on the developing lymphocyte, and in this regard it is interesting that some have shown that gonadal hormones have a profound effect on lymphopoiesis [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In B-CLL, P-glycoprotein expression is felt to be intrinsic rather than acquired, reflecting different basal levels of MDR1 expression in the different lymphocyte subsets [16,28,29]. Some of this intrinsic expression may vary as a result of differential influences of hormone levels on the developing lymphocyte, and in this regard it is interesting that some have shown that gonadal hormones have a profound effect on lymphopoiesis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Of note is a recent study which found that the normal homologue of the B-type CLL cell, a tonsillar lymphocyte, expresses Pgp [29]. In these studies, expression of MDR1 was demonstrated using many techniques, including RNA analysis with slot blotting or RT-PCR, flow cytometry using different monoclonal antibodies, and functional studies of dye efflux, usually using rhodamine-123.…”
Section: Introductionmentioning
confidence: 97%
“…Reverse transcription (RT) was performed with a first-strand cDNA kit following the protocol recommended by the manufacturer (Life Technologies). (61). The cycling parameters consisted of 95°C for 60 s, followed by 32 cycles at 95°C for 60 s, 58°C for 60 s, and 72°C for 60 s and 1 cycle at 72°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…However, an MDR + phenotype in CLL does not appear to correlate with either staging and clinical parameters (66,72), and/or in vivo or in vitro sensitivity to drugs (73). Expression of p-glycoproteins has been documented in CD19 + CD5 + B cells from tonsils and blood in normal individuals (71,74), and it has been suggested that p-glycoprotein expression may be an inherent characteristic of CLL cells.…”
Section: Multidrug Resistance Phenotypementioning
confidence: 99%